Effect of quenching media on mechanical properties of welded mild steel plate - Taiwo Semiu Amosun; Saheed Olalekan Hammed; Antônio Marcos Gonçalves de Lima; Ilham Habibi (Universitas Muhammadiyah Magelang, 2023)
Quenching is a swift way of returning metal back to ambient temperature in order to acquire a certain property. Although it is often used to enhance the hardness of metals and their micro-structure, it equally causes a serious variation in the mechanical and physical properties of the metals. This research focuses on quenching media's effect on the microstructure and mechanical properties of a 150mm x 80mm x 8mm welded mild steel plate through microscopic examination, metallography mounting, surface grinding, and surface polishing. Microstructural analysis with hardness and impact test was carried out on the steel plate using water, air, and oil as the quenching media. The results of the test show the Vickers Pyramid Number (HV) for water, oil, and air to be 284.2, 270.9, and 262.2 HV for the base metal, heat affected zone (HAZ), and weld metal (WM), respectively. The amount of energy absorbed by the three specimens during fracture is 23.12, 25.27, and 26.83 J, respectively. The test further indicates that the water-quenched media exhibited mostly martensitic structures and held back austenite with many structures of cementite while the oil and air media exhibited martensite phase and refined grains structures individually. It is therefore concluded that air is more suitable to cool the weld metal for damping applications in engineering.